Timing and extent of crop damage by wild pigs (Sus scrofa Linnaeus) to corn and peanut fields. (July 2020) - Boyce, C.M.; VerCauteren, K.C.; Beasley, J.C.
Abstract: The global expansion of wild pigs over the last few decades has resulted in an increase in extent and distribution of damages to crops, placing a growing strain on agricultural producers and land managers. Despite the extent of wild pig damage to agriculture, there is little data regarding timing and spatial variability of damage to corn ( Zea mays Linnaeus) and we found no data regarding the effect of these factors on peanuts ( Arachis hypogaea Linnaeus). Our objective was to determine the timing and extent of wild pig damage to corn and peanut fields, as well as the extent to which local habitat attributes are useful predictors of damage to these crops. During 2017–2018 we performed ground-based surveys throughout the growing season for 29 corn and 41 peanut fields in South Carolina, USA to determine the most important growth stages for wild pig depredation in both crops. Damage to corn peaked shortly after planting during the seedling stage, fell to nearly zero during V4–V6 stages, and resumed during the silk and mature stages. Peanut damage was almost exclusively limited to the seedling stage. Landscape models for both crops identified the extent of forested and wetland areas surrounding crop fields as the most important attributes positively associated with wild pig damage, while the amount of adjacent agricultural area and paved roads were associated negatively. The number of wild pigs identified by remote cameras also was an important indicator of the extent of damage to peanut fields. Results suggest management efforts to limit crop depredation by wild pigs should be targeted shortly prior to planting. Further, because damage was positively associated with the availability of wetland and forest habitats, our results suggest agricultural damage by wild pigs may be most severe near areas of preferred native habitats. Highlights: Wild pig damage to corn and peanuts varied significantly among plant growth stages. Majority of wild pig damage occurred at the emergence stage for both crops. Greater area of forests and wetlands adjacent to fields was associated with more damage. Adjacent agricultural area and presence of paved roads were associated with lower damage.